As formas geométricas em livros para pré-leitores - Martins, Diana Maria (2021)
The aim of this brief study is to present a critical reading of four books aimed at pre-readers whose common theme is the approximation to the concepts of forms. The supply of the book market aimed at babies and very young children in Portugal, in fact, corresponds to a sector that, in the last decades, has enjoyed a strong growth, showing a very diverse form(s) even though sometimes with a very variable quality. The scarcity of academic studies focused on this field motivates the realization of our concise analysis. A characterization of these books will be made, especially for training purposes and a reflection around the characteristics of their potential readers, followed by a discussion centered on an exemplary corpus, through the use of analysis tools and key concepts specific to the child's studies, but also from literary studies, in particular children’s literature, design, illustration, as well as developmental psychology, given the relevance of knowledge of children's cognitive development (stage of personality development) in the development of reading itself (stage of development and type of reading).